(untitled) (Psychology Travelogs, 2024)
The article presents a theoretical analysis of socio-psychological adaptation of a creative personality. It`s devoted to highlighting the results of scientific development of the problem of personality anxiety in the context of its social and psychological adaptation and realization of creative potential. The importance of the topic determines the constant complication of human adaptation processes in connection with anxiety, characteristic of the modern world. The chronicle of anxiety exacerbates the issue of human preservation, search for ways of survival, rehabilitation and development. The article reveals the relationship between a person’s creative potential and anxiety, and the idea of the role of anxiety in the process of its adaptation were considered based on a review of the works of philosophers – existentialists, representatives of psychodynamic approaches, and modern researchers. It is pointed out the need to develop a person’s creative potential through awareness of the essence of their anxiety and understanding of its true causes. It is on this basis that successful adaptation is possible. The main idea of the article is to consider anxiety as a psychological phenomenon, the potential of which unfolds on a continuum from an internal energy drive with the function of a creative impulse to a painful formation that underlies depression and psychosomatic disorders. Thus, anxiety performs two functions in the process of human adaptation. The authors of the article see in the creative potential of the individual a significant reserve of human civilization, the leading force of progressive development of each person and productive adaptation to current social and psychological conditions of reality. Creative activity appears as the same mechanism that opposes regressive lines in human development, can be a highly capable means of psychological rehabilitation and preservation of psychological health.